Vitamin D, Hormonal profiles and Homa-IR in Polycystic Ovary Syndrome (PCOS) Women who are candidates for In Vitro Fertilization at a Tertiary Hospital in Western Kenya - Linge, Kavoo; Cyprian , Kavoo Linge Mabonga (African Journal of Education,Science and Technology (AJEST), 2024)
Polycystic Ovary Syndrome (PCOS) is a condition that presents with high androgens levels, disturbances in menstrual cycles and polycystic ovaries in shape. Studies report of 30% to 80 % of PCOS gets insulin resistance, hyperinsulinemia and type II diabetes mellitus. It is one of the most common cause of infertility and thus lowering their quality of life. Research is emerging that 70 % of PCOS patients do have Vitamin D deficiency, whether there is a connection between Vitamin D and insulin resistance in PCOS, studies have remained inconsistent and inconclusive. To compare the insulin resistance, hormonal profiles and Vitamin D levels in PCOS women who are candidates for IVF at a tertiary hospital. A case control study carried out between June 2023 and April 2024 at Mediheal Fertility Centre and MTRH in Eldoret. A sample of 60 women. Group 1 of 20 participants with infertile PCOS diagnosed according to Rotterdam criteria and group II of 20 women who are fertile without PCOS and group III of 20 infertile non PCOS who are also candidates for IVF served as controls. Luteinizing hormone, Testosterone, Ant Mullerian hormone, Insulin, fasting blood sugar and Vitamin D levels were carried out using automated Chemiluminescence (ECLIA) methods at MTRH. Data was analyzed using STATA version 15 and Wilcoxon rank-sum test. P values set at <0.05.AMH, Testosterone, LH and Insulin hormone levels were significantly higher as compared to fertile non PCOS and infertile non PCOS p<0.05. However, Vitamin D was significantly lower in infertile PCOS as compared to fertile non PCOS and infertile non PCOS p< 0.05. Vitamin D correlated negatively with LH and Testosterone but positively with AMH and Insulin suggesting that higher levels of LH and Testosterone are linked to lower levels of Vitamin D unlike AMH and Insulin though the correlation was not statistically significant p> 0.05. HOMA-IR, HbA1C and fasting blood sugar were significantly higher in infertile PCOS as compared to fertile non PCOS and infertile non PCOS p< 0.05. Vitamin D correlated negatively with HbA1C but positively with HOMA-IR though not statistically significant p> 0.05. Further research may be warranted to explore additional factors influencing IR and randomized clinical trials to test impact of Vitamin D on metabolic dysregualtions. Healthcare professionals should ensure adequate Vitamin D levels in patients to potentially mitigate insulin resistance.